Do early non-steroidal anti-inflammatory drugs for analgesia worsen acute kidney injury in critically ill trauma patients? An inverse probability of treatment weighted analysis. Issue 4 (October 2020) - Hatton, Gabrielle E.; Bell, Cynthia; Wei, Shuyan; Wade, Charles E.; Kao, Lillian S.; Harvin, John A.
Abstract : BACKGROUND: Administration of nonsteroidal anti-inflammatory drugs (NSAIDs) for acute posttraumatic analgesia is increasing in popularity as an alternative to opioids despite reservations regarding its potential impact on the development of acute kidney injury (AKI). We hypothesized that early NSAID administration for analgesia would be associated with worsened renal function in severely injured trauma patients. METHODS: A retrospective cohort study of severely injured adult (≥16 years) patients admitted to the intensive care unit with ≥1 rib fracture between 2010 and 2017 was performed. The early NSAID group was defined by receipt of one or more doses of NSAID within the first 48 hours of hospitalization. Acute kidney injury diagnosis and staging were defined by the Kidney Disease Improving Global Outcomes Guidelines. The primary outcome was a composite measure of two outcomes within the first week of hospitalization: (1) AKI progression (increase in AKI stage from arrival) or (2) death. Secondary outcomes included AKI progression, AKI improvement, AKI duration, and mortality. Inverse propensity of treatment weights were generated using clinically sound covariates suspected to be associated with the decision to give early NSAIDs and the primary or secondary outcomes. Multivariable analyses were performed adjusting for inverse propensity of treatment weights, covariates, and length of stay. RESULTS: Of 2, 340 patients, 268 (11%) were administered early NSAIDs. When compared with the control group, patients who received early NSAIDs were less severely injured. Renal outcomes were worse in the control group. Standardized mean differences were minimal after weighting. On multivariable analysis, administration of early NSAIDs was not associated with worsened renal outcomes or increased mortality. CONCLUSION: Although only 11% of patients received early NSAIDs after trauma for analgesia, early NSAID exposure was not associated with increased AKI progression, decreased AKI improvement, prolonged duration, or increased mortality. Given the lack of evidence showing harm, early NSAIDs for analgesia may be underused for severely injured patients. LEVEL OF EVIDENCE: Prognostic, level III, Therapeutic, level IV. Abstract : Supplemental digital content is available in the text.